PENGARUH PERILAKU MANAJEMEN LABA DAN KEBIJAKAN DIVIDEN PADA RETURN SAHAM - Sanjaya Adi Pranata, A.A.Gde; Badera, I Dewa Nyoman (E-Jurnal Akuntansi, 2016)
This study has the objective to determine the effect the behavior of earnings management and dividend policy on stock returns. The number of samples was 45 company observations. Data analysis method used is multiple linear regression analysis. Based on the analysis and hypothesis testing, it was found that the behavior of earnings management and dividend policy and the positive effect was statistically significant at stock returns. This shows that the higher the earnings management behavior and policies of dividends, the higher the return of the shares, and vice versa. Stock return is a reflection of a company that the company has shown a good performance to be able to perform its obligation to provide dividends.
Keywords: Earning Management, Divident Police, Return